PERAN DAN FUNGSI KOMUNIKASI MASSA - Qudratullah Qudratullah (Jurnal Dakwah Tabligh, 2016)
This research concentrates with the function and the role of mass communication which has a significant contribution toward people’s life. The objective of this research is to figure out the role and the function of mass communcation. The use of method is qualitative and the technique analysis is about descriptive analysis. The data collected by exploring all literatures related to mass communication. The result of this clarifies that the role and the function of mass communciation are still sticking with their function and role that are live experiencing, communicator, information taker, interactive network, and road mapping. The function is qualified by providing information, education, influencing, and entertainment.